A Study on Socio-Economic Conditions in Haryana –During Mugmal Period: Exploring the Socio-Economic Influence of Haryana during the Mugmal Period (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Haryana is the gateway to the prosperous Gangetic-valley system. Throughout the Sultanate and Mughal periods, the Haryana region acquired a strategic significance from trade and defence point of view. Mahabharata at Kurukshetra in ancient time, and three battles of Panipat, which completely changed the fortune of India, were fought in Haryana. This is the place from where Lord Krishna gave the message of Bhagvadgita to the humanity in the entire world. The saints and seers meditated on the banks of sacred river Sarasvati-that once flowed through the region, and composed famous epics, scriptures and treatises.